The Managerial Performance of Megou Pak Tulang Bawang University - Okta Malinda; Endang Susilowati; Lely Marce Margareta (Research Collaboration Community (RCC), 2022)
The changes in the regulation of accreditation criteria from 7 standards to 9 standards and the inconsistency of the results of previous research regarding the effect of incentives, non-financial performance, and leadership style on managerial performance have become an interest in conducting this research again. This study aims to provide empirical evidence about the effect of incentives, non-financial performance, and leadership style on managerial megou pak tulang bawang university performance. This research was conducted at megou pak tulang bawang university in menggala Lampung with its unit of analysis Good-accredited study program which has 12 study programs, consisting of samples obtained from as many as 121 Lecturer. The sampling technique used was purposive sampling. The data analysis method used is a quantitative method that the multiple regression analysis tested with Statistical Package for the Social Sciences (SPSS) V24. This study's results indicate that incentives consisting of bonuses, rewards, and professional and honor allowances have a significant positive effect on managerial performance. The non-financial performance, which consists of the work and environmental dimensions, has a significant positive effect on managerial performance. Leadership styles which consist of participative style, authoritarian style, and task-oriented style significantly negatively affect managerial performance. The implication of this research is to provide additional indicators such as the professional allowances & honor in incentive variable indicators not only limited to bonuses and rewards.